2021
DOI: 10.1136/bmjopen-2021-049924
|View full text |Cite
|
Sign up to set email alerts
|

Social and structural determinants of injecting-related bacterial and fungal infections among people who inject drugs: protocol for a mixed studies systematic review

Abstract: IntroductionInjecting-related bacterial and fungal infections are a common complication among people who inject drugs (PWID), associated with significant morbidity and mortality. Invasive infections, including infective endocarditis, appear to be increasing in incidence. To date, preventive efforts have focused on modifying individual-level risk behaviours (eg, hand-washing and skin-cleaning) without much success in reducing the population-level impact of these infections. Learning from successes in HIV preven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(39 citation statements)
references
References 93 publications
0
39
0
Order By: Relevance
“…For patients with IDU-IE, unsafe injection drug use is the underlying cause of their infection and addiction treatment should be incorporated into treatment plans for secondary prevention [ 5 , 32 ]. All patients with IDU-IE in Halifax and 92% of patients with IDU-IE in Saint John reported opioid injection [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…For patients with IDU-IE, unsafe injection drug use is the underlying cause of their infection and addiction treatment should be incorporated into treatment plans for secondary prevention [ 5 , 32 ]. All patients with IDU-IE in Halifax and 92% of patients with IDU-IE in Saint John reported opioid injection [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…While one study identified an association between controlled-release hydromorphone prescriptions and IDU-IE in Ontario [ 64 ], a small minority of patients with IDU-IE in Ontario have recent prescriptions for hydromorphone [ 6 , 64 ]. Increasing rates of serious injection drug use-associated bacterial infections have been observed in many jurisdictions [ 4 , 5 ], and in Ontario appear to parallel transitions in the drug supply towards increasing use of illicitly-manufactured fentanyl [ 6 ]. Known risk factors for serious injecting-related infections include more frequent injecting (which has been associated with fentanyl and with stimulants), re-use of contaminated needles and filters, and subcutaneous injecting [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations